2024
DOI: 10.1021/acs.accounts.3c00811
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Recyclable and Nonpersistent Polyethylene-like Polyesters

Marcel Eck,
Stefan Mecking

Abstract: Conspectus Aliphatic polyesters based on long-chain monomers were synthesized for the first time almost a century ago. In fact, Carothers’ seminal observations that founded the entire field of synthetic polymer fibers were made on such a polyester sample. However, as materials, they have evolved only over the past decade. This is driven by the corresponding monomers becoming practically available from advanced catalytic conversions of plant oils, and future prospects comprise a possible generation from third-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Recent work, pioneered by the group of Mecking, has demonstrated that synthesizing novel polymers consisting of isolated ester or ketone linkages embedded within an aliphatic C–C backbone affords recyclable/biodegradable polyolefin-like polymers. 117–119 The insertion of weak linkages into backbones could also be used to convert polyolefin waste into recyclable counterparts while keeping the original properties. For instance, thermochemical oxidation of the polyolefin backbone enables the introduction of various functional groups such as alcohols, ketones, esters and oximes, 56,57,60,120 which could serve as chemical handles for depolymerization reactions.…”
Section: Future Directions and Strategiesmentioning
confidence: 99%
“…Recent work, pioneered by the group of Mecking, has demonstrated that synthesizing novel polymers consisting of isolated ester or ketone linkages embedded within an aliphatic C–C backbone affords recyclable/biodegradable polyolefin-like polymers. 117–119 The insertion of weak linkages into backbones could also be used to convert polyolefin waste into recyclable counterparts while keeping the original properties. For instance, thermochemical oxidation of the polyolefin backbone enables the introduction of various functional groups such as alcohols, ketones, esters and oximes, 56,57,60,120 which could serve as chemical handles for depolymerization reactions.…”
Section: Future Directions and Strategiesmentioning
confidence: 99%